When it matters most: a trauma-informed, outdoor learning programme to support children's wellbeing during COVID-19 and beyond. Issue 2 (3rd April 2021) - Mulholland, Michaela; O'Toole, Catriona
Abstract: This paper presents a unique school-based programme that harnesses the benefits of both trauma-informed practice (TIP) and outdoor environments to support children's social and emotional wellbeing throughout the pandemic and beyond. In the opening sections of the paper, we discuss the extant literature and conceptual underpinning of TIP and outdoor learning, and highlight why both are needed, particularly in the context of Covid-19. We then chart the design of a six-week outdoor trauma-informed programme, devised to support children's emotional regulation and overall sense of wellbeing. The programme activities are aligned to the Northern Ireland curriculum, and are tailored to make use of the outdoor spaces available in the first author's place of work – a primary school in South Belfast. We conclude the paper by highlighting the importance of trauma-informed curriculum and pedagogical innovations and note future directions for trauma-informed schools. Whilst there are many generic guidelines on trauma-informed care in schools, this paper makes a distinct contribution to the field; firstly by demonstrating how teachers can use their craft – teaching – as a component of TIP; and secondly by infusing trauma-informed principles within outdoor learning environments.